Fig. 10. A–C in Hyoliths and small shelly fossils from the Lower Cambrian of North-East Greenland - Malinky, John M.; Skovsted, Christian B. (Zenodo, 2004)
Fig. 10. A–C. "Orthotheca bayonet var. groenlandica (Poulsen, 1932)". A. MGUH 3521; A1, venter; A2, right lateral edge; A3, dorsum. B. MGUH 3523, venter. C. MGUH 3525; C1, dorsum; C2, venter; C3, cross−section. D. "Orthotheca communis (Billings, 1872)", MGUH 3524; D1, cross−section; D2, dorsum; D3, right lateral edge with venter to right; D4, venter. E. "Orthotheca bayonet var. longa (Poulsen, 1932)", MGUH 3526, venter. F. "Orthotheca billingsi (Walcott, 1886)", MGUH 3528, venter. G. Coleolus sp.? MGUH 3517. All specimens from the collections of C. Poulsen. Scale bars 2 mm. Published as part of Malinky, John M. & Skovsted, Christian B., 2004, Hyoliths and small shelly fossils from the Lower Cambrian of North-East Greenland, pp. 551-578 in Acta Palaeontologica Polonica 49 (4) on page 567, DOI: 10.5281/zenodo.13522197